ENHANCING STUDENTS’ READING COMPREHENSION THROUGH DISCOVERY LEARNING METHOD AT THE SEVENTH GRADE OF SMP HARAPAN 3 DELI SERDANG - Nurmahyuni Asrul (FKIP Universitas Al Washliyah Medan, 2023)
The objective of this study was to enhance the reading comprehension of seventh-grade junior high school students through the implementation of the discovery learning method. The research engaged English teachers, school principals, and seventh-grade students from SMP Harapan 3 Deli Serdang. The study encompassed a total of 30 participants, comprising 10 boys and 20 girls. Employing a classroom action research approach, the investigation was executed in two distinct cycles following a pre-test.Â Collaborating closely with English teachers, the researchers conducted the Pedagogical Action (PTK) with a student population of 30. Analysis of the data from both Cycle I and Cycle II led to the following findings: during the pre-test, 10 students achieved a success rate of 33.5%, while 20 students scored a lower rate of 66.5%. In Cycle 1, the success rate increased to 43.5% for 13 students, with a corresponding failure rate of 56.5% among 17 students. In Cycle II, the success rate further improved, as 22 students attained a rate of 73.5%, whereas 8 students encountered a failure rate of 26.5%. In conclusion, this study demonstrates a consistent elevation in student scores, underscoring the effectiveness of the discovery learning method in enhancing reading comprehension among seventh-grade students at SMP Harapan 3 Deli Serdang. The findings indicate that this method holds substantial promise for educators dedicated to nurturing the reading proficiency of their students.